Relação entre a qualidade ambiental e o hábito alimentar de peixes na bacia do rio Itaúnas, ES-Brasil - Silva, Anna Paula Bôa (2019)
This study was developed with the objective of investigate the diet of various fish species in different environments in Itaúnas river basin, aiming to improve the understanding of their ecological interactions in context of the ecosystem. The Itaúnas River basin is part of Mata Atlântica biome, with an area of approximately 4,480 km2 , of which 4,360 km2 is in the state of Espírito Santo and 120 km2 in the state of Bahia. The study area consists of 10 points along the Itaúnas river basin located in cities of Conceição da Barra, Pedro Canário and on border between Pinheiros and Montanha. The collections were performed by intensive and generalized catches from July 2017 to February 2018. The utensils used in the samplings were sieves and trawls. Environmental quality was interpreted through the "Habitat Integrity Index" (HII). A total of 1,742 specimens of fish were collected, distributed in 4 orders, 11 families, 19 genera and 21 species. The diet of the selected species was carried out through food indices, complemented by analyzes of diversity, uniformity, stomach repletion index, condition factor and similarity. A total of 809 stomachs were analyzed, resulting in 60 food items identified for all species and sites studied, with greater expressiveness for autochtonous items. The ichthyofauna diet of this basin is supported mainly by aquatic insects, which are available in large quantities in the environment, what stands out the importance of riparian vegetation integrity as the main supplier of terrestrial resources to support aquatic biota. The Itaúnas river basin has a high rate of degradation, mainly due to deforestation, leading to impoverishment of fish diversity, which, as observed in the study, are more demanding species that consume more specific items of better environments, such as allochthonous items and of rapids, end up being restricted to the most preserved environments that still have the possibility to offer such items.